2008
DOI: 10.1589/jpts.20.255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Infrared Laser on Xylene-induced Acute Inflammation in Mice

Abstract: Abstract.[Purpose] The purpose of the present study was to investigate the effect of magnetic infrared laser (MIL) radiation on the xylene-induced acute inflammation.[Subjects] The subject animals were male ICR mice.[Methods] Mice were once irradiated (60s) by MIL at 1.33, 2.66 or 6.65 J/cm 2 of MIL, or treated with indomethacin or dexamethasone. Then xylene (0.03 ml) was topically applied to the anterior surface of the right ear to induced inflammation 1 h after irradiation with MIL. The changes in ear weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…28 Xylene usually initiates inflammatory response resulting in oedema, warmth and redness of the skin of the ear of mice due to the release of histamine, kinin, fibrinolysin and substance P. [29][30][31][32] In this investigation, Lannea microcarpa extract (ALM) significantly inhibited xylene-induced ear oedema in a dose related manner and ultimately decreased irritation, oedema and erythema effects and so it could be suggested that the extract inhibited the activities of the proinflammatory mediators including histamine, kinins and fibrinolysin. Although the actual mechanism of action of Lannea microcarpa extract (ALM) was not demonstrated in this research, its anti-inflammatory effects may be attributed to one or more of the phytochemicals constituents such as flavonoids, steroids saponins and tannins which were found to be present in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…28 Xylene usually initiates inflammatory response resulting in oedema, warmth and redness of the skin of the ear of mice due to the release of histamine, kinin, fibrinolysin and substance P. [29][30][31][32] In this investigation, Lannea microcarpa extract (ALM) significantly inhibited xylene-induced ear oedema in a dose related manner and ultimately decreased irritation, oedema and erythema effects and so it could be suggested that the extract inhibited the activities of the proinflammatory mediators including histamine, kinins and fibrinolysin. Although the actual mechanism of action of Lannea microcarpa extract (ALM) was not demonstrated in this research, its anti-inflammatory effects may be attributed to one or more of the phytochemicals constituents such as flavonoids, steroids saponins and tannins which were found to be present in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically topical application of xylene causes acute inflammation which is associated with severe vasodilation and edematous changes of skin (Ho et al, 2008;Puerta et al, 1996;Kim et al, 2007;Kou et al, 2003;Rotelli et al, 2003). According to present findings (Table 3), it can be claimed that the extract of C. inerme may exhibit anti-inflammatory activity through reducing vasodilation as well as improving edematous condition.…”
Section: Discussionmentioning
confidence: 54%
“…Because the allergic dermatitis evoked by DNFB shows phenomena similar to general inflammatory responses [3][4][5] and MIL has anti-inflammatory effects [16][17][18][19] , we considered that MIL irradiation would be ameliorated DNFB-induced contact dermatitis. In the present study, contact dermatitis was induced in mice by sensitization with DNP-OVA followed by DNFB challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence that MIL treatments ameliorate type I allergic dermatitis corresponds well to the clinical indications of MIL in the various inflammatory diseases [16][17][18] . These beneficial effects of MIL on the DNFB-induced dermatitis were considered as related with their antioxidant effects, 19,26) . However, the previously reported stimulation of the immune system 27,28) by MIL therapy may also be involved in the beneficial effects on allergic dermatitis activity detected in the present study because immunomodulatory agents can reduce inflammation 29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation